Persepsi Masyarakat tentang Bagi Hasil pada Bank Syariah - Angga Setia Putra, Mukhammad; Yudiantoro, Deny (STKIP PGRI SITUBONDO, 2024)
This study aimed to determine the perceptions of the Bejijong Village community toward the profit-sharing system at Islamic Banks. This type of research uses a qualitative approach by collecting data on the Bejijong Village community and using library materials (library research). Data collection methods are observation, interviews, and documentation. Data analysis methods, namely reducing data, presenting data, and drawing conclusions. The knowledge of the people of Beijing Village about profit sharing is still relatively low because apart from not having never been a customer at an Islamic bank, the community also admits that they have received insufficient information or socialization regarding this profit sharing. This lack of understanding is one of the factors influencing the perceptions of most people in Bejijong Village so that they still think or suspect that the profit sharing and interest used by conventional banks are not much different and cause people not to be very interested in using sharia banking services and services.